2022
DOI: 10.1002/2211-5463.13022
|View full text |Cite
|
Sign up to set email alerts
|

Prefoldin subunit 6 of Plasmodium falciparum binds merozoite surface protein‐1

Abstract: Malaria is a human disease caused by eukaryotic protozoan parasites of the Plasmodium genus. Plasmodium falciparum (Pf) causes the most lethal form of human malaria and is responsible for widespread mortality worldwide. Prefoldin is a hetero-hexameric molecular complex that binds and delivers unfolded proteins to chaperonin for correct folding. The prefoldin PFD6 is predicted to interact with merozoite surface protein-1 (MSP-1), a protein well known to play a pivotal role in erythrocyte binding and invasion by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Merozoite surface protein-1 (MSP-1) of Pf plays an essential role in the binding of merozoites to human erythrocytes and infecting erythrocytes. Pf PFD6 was shown to interact with MSP-1 suggesting that Pf PFD6 might stabilize and assist the trafficking of MSP-1, which indirectly promotes erythrocyte invasion and pathogenicity of malaria ( Kumar et al, 2020 ).…”
Section: Implications Of Prefoldin In Pathological Conditionsmentioning
confidence: 99%
“…Merozoite surface protein-1 (MSP-1) of Pf plays an essential role in the binding of merozoites to human erythrocytes and infecting erythrocytes. Pf PFD6 was shown to interact with MSP-1 suggesting that Pf PFD6 might stabilize and assist the trafficking of MSP-1, which indirectly promotes erythrocyte invasion and pathogenicity of malaria ( Kumar et al, 2020 ).…”
Section: Implications Of Prefoldin In Pathological Conditionsmentioning
confidence: 99%
“…Plasmodium falciparum 3D7 (Pf 3D7) PFD subunits, namely Pf PFD1 (20 kDa), Pf PFD2 (19 kDa), Pf PFD3 (24 kDa), Pf PFD4 (17 kDa), Pf PFD5 (30 kDa) and Pf PFD6 (16 kDa), were cloned in pET-28a (+) and over-expressed in E. coli strain BL21-DE3. Recombinant 6x-His- Pf PFD (r Pf PFD) subunits were purified using Ni-NTA resin, as described previously (Kumar et al, 2022a) (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that MSP-1 is a substrate of Pf PFD6 (Kumar et al, 2022a). MSP-1 is a critical molecule in the parasite egress and invasion of fresh RBCs.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the P. berghei blood stage appears not to be substantially affected by the loss of Pb PCS5 implies marked differences in nuclei distribution and microtubule organization in mosquito and blood stages or some redundancy in the prefoldin complex organization only in blood stage development. In fact, subunit 6 of prefoldin was already described to bind to merozoite surface protein 1 (MSP1) during P. falciparum blood stage development (Kumar et al., 2020). MSP1 is a major surface protein of merozoites and is explored as a vaccine (Blank et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the putative prefoldin complex subunit 5 ( Pb PCS5, PBANKA_0920100) gene, encoding for the Pb PCPS5 protein showed a drastic block in liver stage development (log 2 ‐fold reduction = −7.404), which correlates with an increased expression level of Pb PCS5 mRNA during parasite liver stage development observed by RNA seq analysis (Table 1) (Caldelari et al., 2019; Otto et al., 2014). A recent study showed that subunit 6 of the prefoldin complex of P. falciparum interacts with merozoite surface protein 1 ( Pf MSP1) during the late stages of asexual blood development (Kumar et al., 2020). Prefoldin is a heterohexameric chaperone complex known to be involved in the assembly and maintenance of actin as well as α‐ and β‐tubulins in a wide range of eukaryotes such as yeast, C. elegans and Arabidopsis (Gao et al., 1992; Lundin et al., 2008; Martín‐Benito et al., 2002; Rodríguez‐Milla & Salinas, 2009; Yaffe et al., 1992).…”
Section: Introductionmentioning
confidence: 99%